Low-temperature drying porcelain-imitating waterproof sculpture pottery and preparation method thereof

CN122916604APending Publication Date: 2026-10-16ZHENJIANG COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611226770.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]目前,市面上主流免烧雕塑黏土分为石膏纸基风干陶土、PVC石塑黏土和普通丙烯酸风干黏土三类,其中,石膏纸基风干陶土是以石膏、植物纤维为主体,自然风干成型,其可塑性优良、大件不易开裂,但是坯体内部多孔,本体不具备防水能力,成品必须多层涂刷清漆、环氧树脂做封闭防水,漆膜磨损后极易吸水软化、掉粉,户外使用寿命短;整体硬度偏低,磕碰易破损,达不到陶瓷坯体质感;PVC石塑黏土主要是以聚氯乙烯树脂、无机石粉为原料,需要100℃以上高温烘烤固化,薄件细节表现力强,但是其实心厚坯烘干收缩极大,极易内部炸裂开裂,无法制作5cm以上大型雕塑并且烘烤后完全硬化不可二次修补修改,创作容错率极低;另外,普通丙烯酸风干黏土主要是依靠白乳胶做粘结剂,其成本低廉,但是防潮性极差,南方潮湿环境极易发霉、变软坍塌,硬度不足,耐磨性能差;由此可见,现有技术中的石膏纸基风干陶土、PVC石塑黏土和普通丙烯酸风干黏土,虽然都各具不同的优势,但是均存在各种各样的缺陷,因此,无法同时兼顾手工可塑、低温固化、本体通体防水、高硬度、厚大件抗裂、可二次修改等重要特性

Benefits of technology

[0021](1)通过采用上述质量份数的高岭土、超细石英粉、煅烧滑石粉以及纳米碳酸钙作为无机瓷质填料,不但利用上述质量份数的高岭土赋予泥料基础泥塑可塑性,使其成品哑光素瓷质感,细腻平整,同时利用相应比例的超细石英粉提升固化后坯体硬度、耐磨度以及物理强度,再者,利用合理比例的煅烧滑石粉:降低了烘干整体收缩率,解决厚坯内外干湿不均开裂问题,同时采用适配比例的纳米碳酸钙,使其微调泥料软硬手感,提升了精细雕刻细节表现力;再加上固含量为25%~35%的特定质量份数的中性硅溶胶,利用中性硅溶胶与环氧改性丙烯酸乳液协同作用,显著降低了吸水率,具备优异的抗渗水性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses low-temperature drying imitation porcelain waterproof sculpture pottery clay and a preparation method thereof. Raw material composition and mass ratio are as follows: inorganic porcelain filler 65-80 parts; neutral silica sol with solid content of 25%-35% 8-13 parts; silane coupling agent KH560 0.1-0.6 parts; epoxy modified acrylic emulsion with solid content of 35%-45% 8-15 parts; functional additive 1.5-4.0 parts; wherein, the inorganic porcelain filler comprises: kaolin 28-42 parts, ultra-fine quartz powder with particle size of 1500-2500 meshes 15-25 parts, calcined talc powder 8-16 parts, nano calcium carbonate 3-8 parts; the functional additive comprises: short-cut plant cellulose fiber, glycerol, silicone defoaming agent, water-based mildew-proof agent, dispersing agent. Advantages are as follows: the drying overall shrinkage is reduced, the problem of uneven dry-wet cracking inside and outside thick body is solved, nano calcium carbonate with a suitable proportion is adopted, the hardness of the mud is finely adjusted, the performance of fine carving details is improved, and the water absorption is significantly reduced, and the anti-permeability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite sculptural clay that can be formed without high-temperature firing and low-temperature drying, has a waterproof body, high hardness and does not crack. Specifically, it is a low-temperature dried imitation porcelain waterproof sculptural clay and its preparation method suitable for making clay figurines, reliefs, ceramic vessels, cultural and creative ornaments and large outdoor intangible cultural heritage sculptures. It belongs to the fields of intangible cultural heritage sculptural materials and handmade clay technology. Background Technology

[0002] Currently, the mainstream non-fired sculpting clays on the market are divided into three categories: gypsum paper-based air-dried clay, PVC stone-plastic clay, and ordinary acrylic air-dried clay. Among them, gypsum paper-based air-dried clay is mainly composed of gypsum and plant fibers, and is naturally air-dried. It has excellent plasticity and is not prone to cracking in large pieces. However, the body is porous and does not have waterproof capabilities. The finished product must be coated with multiple layers of varnish and epoxy resin for sealing and waterproofing. After the paint film is worn, it is very easy to absorb water, soften, and flake off, resulting in a short outdoor lifespan. The overall hardness is relatively low, making it easy to break from impacts, and it does not achieve the texture of a ceramic body. PVC stone-plastic clay is mainly made of polyvinyl chloride resin and inorganic stone powder. It needs to be baked and cured at a high temperature of over 100°C. It has strong detail expression in thin pieces, but its core is not very solid. Thick blanks shrink significantly during drying, making them prone to internal cracking and making it impossible to create large sculptures over 5cm in height. Furthermore, once fully hardened after baking, they cannot be repaired or modified, resulting in a very low margin for error in creation. Additionally, ordinary acrylic air-dried clay relies primarily on white glue as a binder, which is inexpensive but has extremely poor moisture resistance. In humid southern environments, it is prone to mold, softening, and collapsing, and it lacks hardness and wear resistance. Therefore, while existing technologies such as gypsum paper-based air-dried clay, PVC stone-plastic clay, and ordinary acrylic air-dried clay each have their own advantages, they all suffer from various drawbacks. Consequently, they cannot simultaneously achieve the important characteristics of being malleable by hand, curing at low temperatures, being waterproof throughout, having high hardness, being crack-resistant for thick and large pieces, and allowing for secondary modifications. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide a low-temperature dried imitation porcelain waterproof sculpting clay and its preparation method that can simultaneously take into account important characteristics such as hand-plasticity, low-temperature curing, waterproof throughout the body, high hardness, crack resistance of thick and large parts, and secondary modification.

[0004] To solve the above-mentioned technical problems, the low-temperature drying imitation porcelain waterproof sculpting clay of the present invention has the following raw material composition and mass ratio: 65-80 parts of inorganic ceramic filler; 8-13 parts of neutral silica sol with a solid content of 25%-35%; 0.1-0.6 parts of silane coupling agent KH560; 8-15 parts of epoxy-modified acrylic emulsion with a solid content of 35%-45%; and 1.5-4.0 parts of functional additives.

[0005] The inorganic ceramic filler includes: 28-42 parts of kaolin with a particle size of 1000-1500 mesh, 15-25 parts of ultrafine quartz powder with a particle size of 1500-2500 mesh, 8-16 parts of calcined talc powder, and 3-8 parts of nano-calcium carbonate; the functional additives include: chopped plant cellulose fibers, glycerol, organosilicon defoamer, water-based mildew inhibitor, and dispersant.

[0006] The chopped plant cellulose fibers are 1-5 mm in length and are added in an amount of 0.5-3.0 parts; the glycerol is added in an amount of 0.3-1.0 parts; the silicone defoamer is added in an amount of 0.1-0.5 parts; the water-based mildew inhibitor is added in an amount of 0.1-0.5 parts; and the dispersant is added in an amount of 0.1-0.5 parts.

[0007] The inorganic ceramic filler comprises 70-75 parts; neutral silica sol with a solid content of 28%-32% comprises 9-11 parts; silane coupling agent KH560 comprises 0.2-0.4 parts; epoxy modified acrylic emulsion with a solid content of 38%-42% comprises 10-12 parts; functional additives comprises 2.0-3.5 parts; the inorganic ceramic filler comprises 32-38 parts of 1250 mesh kaolin, 17-23 parts of 2000 mesh ultrafine quartz powder, 10-14 parts of calcined talc powder, and 4-6 parts of nano calcium carbonate.

[0008] When used for making large sculptures and thick reliefs with a thickness of 5-10cm, the amount of chopped plant cellulose fiber added is 1.5-2.5 parts, the amount of kaolin is 33-37 parts, and the amount of ultrafine quartz powder is 18-22 parts.

[0009] When making thin-walled vessels and small cultural and creative ornaments with a thickness of ≤2cm, the amount of chopped plant cellulose fiber added is 0.5-1.2 parts, the amount of kaolin is 38-42 parts, and the amount of ultrafine quartz powder is 13-17 parts.

[0010] A method for preparing the above-mentioned low-temperature dried imitation porcelain waterproof sculpting clay includes the following steps:

[0011] S1: Dry powder premixing: Put kaolin, ultrafine quartz powder, calcined talc powder, nano calcium carbonate and short-cut plant cellulose fibers into a mixing container and stir at low speed for 3 to 8 minutes to fully mix all solid powders and obtain a uniform dry powder mixture.

[0012] S2: Liquid phase preparation: Mix neutral silica sol, epoxy modified acrylic emulsion, silane coupling agent KH560, glycerol, organosilicon defoamer, water-based mildew inhibitor, and dispersant, and stir at room temperature for 1-3 minutes to obtain a homogeneous liquid phase mixture;

[0013] S3: Mixing and maturation: Slowly and evenly pour the liquid mixture obtained in step S2 into the dry powder mixture obtained in step S1, stir at low speed for 8-15 minutes to form a clay ball, knead for 3-8 minutes to remove internal air bubbles, seal and keep away from light to mature for 1-3 hours, and the finished sculpting clay is obtained.

[0014] The finished clay sculpture obtained in step S3 is sealed and stored in a sealed bag at room temperature away from light for 30 to 60 days.

[0015] After the clay sculpture is shaped, it needs to undergo low-temperature segmented drying and curing treatment. The specific process is as follows:

[0016] A. Pre-drying: After shaping, place in a well-ventilated environment at room temperature for 18-30 hours;

[0017] B. Segmented and stepped drying: Oven heating rate ≤10℃ / h;

[0018] For small parts with a thickness of ≤2cm: dry at a constant temperature of 40~50℃ for 5~8h; for large parts with a thickness of 5~10cm: keep warm at 40~50℃ for 6~10h, and then heat up to 70~80℃ at a uniform rate and keep warm for 10~15h.

[0019] C. Natural cooling: After drying, the oven is sealed and allowed to cool naturally to room temperature before removing the finished product.

[0020] The advantages of this invention are:

[0021] (1) By using the above-mentioned mass fractions of kaolin, ultrafine quartz powder, calcined talc powder and nano calcium carbonate as inorganic ceramic fillers, not only does the above-mentioned mass fraction of kaolin give the clay the basic plasticity of the clay, making the finished product have a matte porcelain texture that is delicate and smooth, but also the corresponding proportion of ultrafine quartz powder improves the hardness, wear resistance and physical strength of the solidified body. Furthermore, the reasonable proportion of calcined talc powder reduces the overall shrinkage rate during drying, solves the problem of uneven drying and cracking inside and outside the thick body, and the appropriate proportion of nano calcium carbonate is used to finely adjust the softness and hardness of the clay, improving the expressiveness of fine carving details. In addition, a specific mass fraction of neutral silica sol with a solid content of 25% to 35% is used. The synergistic effect of neutral silica sol and epoxy modified acrylic emulsion significantly reduces the water absorption rate and has excellent water resistance.

[0022] (2) By selecting the inorganic ceramic filler and neutral silica sol in the above proportion, KH560 silane coupling agent is added, and the wettability and dispersibility of inorganic powder in organic emulsion are improved, thus enhancing toughness and waterproof long-term performance. At the same time, a specific amount of epoxy modified acrylic emulsion with a solid content of 35% to 45% is added to make the mud material extensible, non-sticky and easy to knead in the wet state. After drying and cross-linking, the impact toughness of the green body is improved, thus avoiding the brittleness of pure inorganic materials.

[0023] (3) The above proportions of short-cut plant cellulose fiber, glycerol, organosilicon defoamer, water-based mildew inhibitor and dispersant are selected as functional additives. The cellulose fiber content significantly reduces the probability of drying cracks in thick and large parts, and the multi-layer structure restrains the shrinkage deformation. At the same time, the glycerol content can keep the clay moist for a long time. The clay will not form a hard skin after being sealed and stored at room temperature for 45 days, and the carving is smooth. The combination of defoamer, dispersant and mildew inhibitor eliminates air bubbles in the clay, the powder is uniform and does not clump, and it does not mold after long-term storage.

[0024] (4) The raw materials are composed of inorganic ceramic fillers, silica sol waterproof system, epoxy acrylic flexible binder and various functional additives. The finished clay is obtained by dry powder mixing, liquid phase adjustment and kneading and maturation. The preparation method is reasonable, low temperature curing and equipment threshold is very low: no ceramic high temperature kiln is required (usually above 1000℃), and it can be cured and shaped by low temperature segment drying at 45~75℃. A three-dimensional inorganic waterproof network is formed by cross-linking silica sol and silane coupling agent, which significantly reduces the water absorption rate of the blank and does not require additional sealing paint in the later stage. The hardness of the finished product is close to very high, the drying shrinkage rate of thick parts is low and it is not easy to crack. The wet clay is smooth and non-sticky, and can be finely shaped. It can be repaired and adjusted twice by wetting and softening with degumming agent or water-based softener. It is also environmentally friendly and non-toxic, and has stable storage. It is suitable for use in all scenarios of intangible cultural heritage teaching, large-scale sculpture and cultural and creative mass production. Detailed Implementation

[0025] The low-temperature drying imitation porcelain waterproof sculpting clay of the present invention comprises the following raw material composition and mass ratio: 65-80 parts of inorganic ceramic filler; 8-13 parts of neutral silica sol with a solid content of 25%-35%; 0.1-0.6 parts of silane coupling agent KH560; 8-15 parts of epoxy-modified acrylic emulsion with a solid content of 35%-45%; and 1.5-4.0 parts of functional additives. The inorganic ceramic filler includes: 28-42 parts of kaolin with a particle size of 1000-1500 mesh; 15-25 parts of ultrafine quartz powder with a particle size of 1500-2500 mesh; 8-16 parts of calcined talc powder; and 3-8 parts of nano-calcium carbonate. The functional additives include: chopped plant cellulose fibers, glycerol, organosilicon defoamer, water-based mildew inhibitor, and dispersant. This low-temperature drying imitation porcelain waterproof sculpting clay... This clay requires no high-temperature ceramic kiln; it can be cured in a regular electric oven. It can be mass-produced in art studios, intangible cultural heritage workshops, and rural research studios, consuming far less energy than firing ceramics, thus meeting the requirements of low-carbon rural revitalization and the cultural and creative industry. The finished product requires no additional layers of waterproof varnish, simplifying the creation process and avoiding the problem of aging and peeling of the varnish film later. It can be used to create large outdoor intangible cultural heritage sculptures and reliefs, as well as small cultural and creative figurines and ceramic containers, making it suitable for clay sculpting teaching, IP derivative development, and mass production of rural cultural and creative products. Thick blanks have low shrinkage and an extremely low probability of cracking. The dried product can be softened and reused. Repairing and adjusting significantly reduces the scrap rate of sculptures; all raw materials are commercially available industrial powders and emulsions, with controllable unit prices for batch production, suitable for commercial mass production; the formula is free of formaldehyde, heavy metals, and harmful substances from PVC, making it safe and non-toxic for children's art education and intangible cultural heritage research. In particular, through the synergistic enhancement of the rigid and flexible interpenetrating structure of ultrafine quartz powder, the inorganic network of silica sol, and the organic network of epoxy-modified acrylic emulsion, the finished product's compressive strength can reach 23-25 ​​MPa, approaching the physical strength of low-temperature fired stoneware, with high surface hardness, good wear resistance, and excellent crack resistance for thick and large pieces: through The synergistic effect of three anti-cracking mechanisms—calcined talc powder reducing shrinkage, short-cut cellulose fibers providing three-dimensional reinforcement to restrain drying shrinkage deformation, and a segmented, stepped drying process controlling the gradient evaporation of moisture—results in an overall drying shrinkage rate of less than 2.2%, and a drying cracking probability of less than 10% for large pieces with a thickness of 5-10cm. This process offers high tolerance for errors and allows for secondary modifications: the wet clay is smooth and non-sticky, allowing for fine shaping; after drying, the finished piece, when moistened with a degumming agent (or water-based softener), can swell on the surface to restore some plasticity, supporting localized secondary clay repair and modification, significantly reducing the scrap rate of sculpture creation.

[0026] The following detailed description, in conjunction with specific embodiments, further illustrates the low-temperature drying imitation porcelain waterproof sculpture clay and its preparation method of the present invention.

[0027] Example 1: Preparation of Special Formula Clay for Large Sculptures and Reliefs

[0028] Weigh the raw materials according to the following parts by weight:

[0029] 35 parts of 1250 mesh kaolin, 20 parts of 2000 mesh ultrafine quartz powder, 12 parts of calcined talc powder, and 5 parts of nano calcium carbonate;

[0030] 10 parts of neutral silica sol (particle size 10-20nm) with 30% solid content; 0.3 parts of silane coupling agent KH560; 11 parts of epoxy-modified acrylic emulsion with 40% solid content; 2 parts of 2mm short-cut plant cellulose fibers; 0.6 parts of glycerol; 0.2 parts of silicone defoamer; 0.2 parts of water-based mildew inhibitor; and 0.2 parts of dispersant.

[0031] The preparation steps are as follows:

[0032] Step S1: Dry powder premixing:

[0033] Add 35 parts of kaolin, 20 parts of ultrafine quartz powder, 12 parts of calcined talc powder, 5 parts of nano calcium carbonate, and 2 parts of 2mm short-cut plant cellulose fiber into a mixing container and stir at low speed for 5 minutes to fully mix all solid powders and obtain a dry powder mixture.

[0034] Step S2: Liquid phase preparation:

[0035] Ten parts of neutral silica sol, 11 parts of epoxy-modified acrylic emulsion, 0.3 parts of silane coupling agent KH560, 0.6 parts of glycerol, 0.2 parts of silicone defoamer, 0.2 parts of water-based mildew inhibitor, and 0.2 parts of dispersant were added to another container and stirred at room temperature for 1 minute to obtain a homogeneous liquid phase mixture. KH560 was pre-hydrolyzed in anhydrous ethanol / acetone or other organic solvents before being mixed with the emulsion. The dispersant can prevent the agglomeration of ultrafine quartz powder and nano-calcium carbonate in the liquid phase.

[0036] Step S3: Mixing and maturation:

[0037] Slowly and evenly pour the liquid mixture obtained in step S2 into the dry powder mixture obtained in step S1, stir at low speed for 10 minutes to form a clay ball, take it out and knead it manually for 5 minutes to remove internal air bubbles, seal it and let it stand in the dark for 2 hours to mature, and you will get the finished sculpting clay.

[0038] The resulting mud is placed in a thickened, sealed plastic bag and stored at room temperature away from light.

[0039] The clay obtained in this embodiment is suitable for making large human figure sculptures, reliefs, and large animal sculptures with a thickness of 5-10cm. It has a high cellulose fiber content, the best crack resistance, and high toughness after drying, making it less prone to breakage when bumped.

[0040] Example 2: Preparation of Special Formula Clay for Small Cultural and Creative Items and Thin-walled Vessels

[0041] Weigh the raw materials according to the following parts by weight:

[0042] 40 parts of 1250 mesh kaolin, 15 parts of 2000 mesh ultrafine quartz powder, 12 parts of calcined talc powder, 5 parts of nano calcium carbonate; 10 parts of neutral silica sol (particle size 10-20 nm) with a solid content of 30%; 0.3 parts of silane coupling agent KH560; 11 parts of epoxy-modified acrylic emulsion with a solid content of 40%; 0.8 parts of 2 mm short-cut plant cellulose fiber, 0.6 parts of glycerol, 0.2 parts of organosilicon defoamer, 0.2 parts of water-based mildew inhibitor, and 0.2 parts of dispersant.

[0043] The preparation steps are the same as in Example 1.

[0044] The clay obtained in this embodiment is suitable for making thin-walled vessels, small cultural and creative ornaments and exquisite figurines with a thickness of ≤2cm. The proportion of kaolin is increased, the proportion of quartz powder is reduced, and the amount of cellulose fiber is reduced. The clay is extremely fine, with no grainy texture on the surface, and has a very high degree of polishing. The ultra-thin shape will not break after drying.

[0045] Example 3: Low-temperature drying and curing of large sculptures and relief clay

[0046] The clay obtained in Example 1 was molded into a human figure sculpture with a thickness of approximately 8 cm, and then dried and cured according to the following process:

[0047] Pre-drying: After shaping, place in a room temperature and ventilated environment for 24 hours to allow the free moisture on the surface of the blank to evaporate naturally, avoiding surface bulging or cracking caused by subsequent rapid drying.

[0048] Segmented step drying: Place the green body into an electric heating oven and control the heating rate at 8℃ / h; first, keep it at a constant temperature of 45℃ for 8 hours, and then raise the temperature at a uniform rate to 75℃ and continue to keep it at that temperature for 12 hours.

[0049] Natural cooling: After drying, the oven is sealed and allowed to cool naturally to room temperature before the finished product is removed.

[0050] The finished sculpture was tested and found to have a compressive strength of 24-25 MPa, an overall drying shrinkage rate of about 1.8%, no cracks on the surface and cross-section of the blank, and extremely low water absorption rate after immersion in water for 72 hours (no obvious weight gain observed by the naked eye). The surface does not soften or shed powder, and it has excellent waterproof performance.

[0051] Example 4: Low-temperature drying and curing of small cultural and creative products

[0052] The clay obtained in Example 2 was molded into a cultural and creative ornament with a thickness of approximately 1.5 cm, and then dried and cured according to the following process:

[0053] Pre-drying: After shaping, place in a well-ventilated environment at room temperature for 20 hours.

[0054] Segmented step drying: Place the green body into an electric heating oven and dry at a constant temperature of 45℃ for 6 hours.

[0055] Natural cooling: After drying, the oven is sealed and allowed to cool naturally to room temperature before the finished product is removed.

[0056] The finished ornaments were tested and found to have a compressive strength of 22-23 MPa, an overall drying shrinkage rate of about 1.5%, a smooth surface without cracks, and no significant weight gain after soaking in water for 72 hours.

[0057] Example 5: Performance Verification of Secondary Repair

[0058] Take the fully dried and cured human figure sculpture obtained in Example 3, and artificially create a scratch about 2mm deep on the surface of the blank. Wet the damaged area with a degumming agent (e.g., water + a small amount of propylene glycol + a trace amount of surfactant). After standing for 5 minutes, the surface clay of the damaged area softens again and regains its plasticity. Take a small amount of fresh clay from Example 1 and fill the scratch, smooth and trim it with a tool, and then dry it again in a 50℃ oven for 4 hours. The repaired area is firmly bonded to the original blank, with no color difference or peeling. The repaired area shows no abnormalities after being soaked in water for 72 hours.

[0059] Comparative Example 1: Commercially available Sculpd air-dried clay

[0060] Take commercially available Sculpd brand air-dried clay, shape it into a test specimen with a thickness of about 5cm, and air-dry it at room temperature for 72 hours until it is completely cured.

[0061] Test results: Compressive strength 9MPa; The blank is not waterproof. After being soaked in water for 24 hours, it shows obvious water absorption, weight gain and softening. It must be coated with varnish to be waterproof; The cracking rate of a 5cm thick blank is 18%; It loses its waterproof ability after the paint film peels off when placed outdoors.

[0062] Comparative Example 2: Commercially available PVC stone-plastic clay

[0063] Take commercially available PVC stone-plastic clay, shape it into a test specimen with a thickness of about 5cm, and bake it at 110℃ for curing according to the product instructions.

[0064] Test results: Compressive strength 20MPa; the blank has a certain degree of water resistance after baking; however, the cracking rate of the 5cm thick blank is as high as 62% or more, and serious shrinkage cracks appear inside; it cannot be repaired or modified after baking and hardening.

[0065] Performance Comparison Summary

[0066] sheet

[0067] The test results show that the clay of this invention has the following properties: hardness: compressive strength 22-25 MPa, equivalent to low-temperature fired red pottery and stoneware; water resistance: the finished product does not absorb water and gain weight, does not soften, and does not shed powder after being immersed in water for 72 hours, requiring no surface sealing paint; shrinkage rate: overall drying shrinkage rate <2.2%, thick blanks do not crack or develop fine cracks; plasticity: it is not sticky when kneaded at room temperature, does not dry and harden quickly when left to stand, and can be repaired by adding clay again after drying and softening; weather resistance: it is permanently stable at room temperature indoors, and does not powder or deform when placed outdoors. Therefore, it is verified that its core indicators such as compressive hardness, water resistance, crack resistance of thick blanks, and secondary repairability are significantly superior to mainstream commercial clay products on the market, and its comprehensive performance meets the expected design goals.

[0068] Of course, the above description is not intended to limit the present invention, and the present invention is not limited to the examples given above. Any changes, modifications, additions or substitutions made by those skilled in the art within the scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A low-temperature dried, porcelain-like, waterproof sculpting clay, characterized in that, The raw material composition and mass ratio are as follows: 65-80 parts of inorganic ceramic filler; 8-13 parts of neutral silica sol with a solid content of 25%-35%; 0.1-0.6 parts of silane coupling agent KH560; 8-15 parts of epoxy-modified acrylic emulsion with a solid content of 35%-45%; and 1.5-4.0 parts of functional additives. The inorganic ceramic filler includes: 28-42 parts of kaolin with a particle size of 1000-1500 mesh, 15-25 parts of ultrafine quartz powder with a particle size of 1500-2500 mesh, 8-16 parts of calcined talc powder, and 3-8 parts of nano-calcium carbonate; the functional additives include: chopped plant cellulose fibers, glycerol, organosilicon defoamer, water-based mildew inhibitor, and dispersant.

2. The low-temperature dried imitation porcelain waterproof sculpting clay according to claim 1, characterized in that: The chopped plant cellulose fibers are 1-5 mm in length and are added in an amount of 0.5-3.0 parts; the glycerol is added in an amount of 0.3-1.0 parts; the silicone defoamer is added in an amount of 0.1-0.5 parts; the water-based mildew inhibitor is added in an amount of 0.1-0.5 parts; and the dispersant is added in an amount of 0.1-0.5 parts.

3. The low-temperature dried imitation porcelain waterproof sculpting clay according to claim 1, characterized in that: The inorganic ceramic filler comprises 70-75 parts; neutral silica sol with a solid content of 28%-32% comprises 9-11 parts; silane coupling agent KH560 comprises 0.2-0.4 parts; epoxy modified acrylic emulsion with a solid content of 38%-42% comprises 10-12 parts; functional additives comprises 2.0-3.5 parts; the inorganic ceramic filler comprises 32-38 parts of 1250 mesh kaolin, 17-23 parts of 2000 mesh ultrafine quartz powder, 10-14 parts of calcined talc powder, and 4-6 parts of nano calcium carbonate.

4. The low-temperature dried imitation porcelain waterproof sculpting clay according to claim 1, characterized in that: When used for making large sculptures and thick reliefs with a thickness of 5-10cm, the amount of chopped plant cellulose fiber added is 1.5-2.5 parts, the amount of kaolin is 33-37 parts, and the amount of ultrafine quartz powder is 18-22 parts.

5. The low-temperature dried imitation porcelain waterproof sculpting clay according to claim 1, characterized in that: When making thin-walled vessels and small cultural and creative ornaments with a thickness of ≤2cm, the amount of chopped plant cellulose fiber added is 0.5-1.2 parts, the amount of kaolin is 38-42 parts, and the amount of ultrafine quartz powder is 13-17 parts.

6. The method for preparing low-temperature dried imitation porcelain waterproof sculpting clay according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Dry powder premixing: Put kaolin, ultrafine quartz powder, calcined talc powder, nano calcium carbonate and short-cut plant cellulose fibers into a mixing container and stir at low speed for 3 to 8 minutes to fully mix all solid powders and obtain a uniform dry powder mixture. S2: Liquid phase preparation: Mix neutral silica sol, epoxy modified acrylic emulsion, silane coupling agent KH560, glycerol, organosilicon defoamer, water-based mildew inhibitor, and dispersant, and stir at room temperature for 1-3 minutes to obtain a homogeneous liquid phase mixture; S3: Mixing and maturation: Slowly and evenly pour the liquid mixture obtained in step S2 into the dry powder mixture obtained in step S1, stir at low speed for 8-15 minutes to form a clay ball, knead for 3-8 minutes to remove internal air bubbles, seal and keep away from light to mature for 1-3 hours, and the finished sculpting clay is obtained.

7. The method for preparing low-temperature dried imitation porcelain waterproof sculpting clay according to claim 6, characterized in that: The finished clay sculpture obtained in step S3 is sealed and stored in a sealed bag at room temperature away from light for 30 to 60 days.

8. The method for preparing low-temperature dried imitation porcelain waterproof sculpting clay according to claim 6, characterized in that: After the clay sculpture is shaped, it needs to undergo low-temperature segmented drying and curing treatment. The specific process is as follows: A. Pre-drying: After shaping, place in a well-ventilated environment at room temperature for 18-30 hours; B. Segmented and stepped drying: Oven heating rate ≤10℃ / h; For small parts with a thickness of ≤2cm: dry at a constant temperature of 40~50℃ for 5~8h; for large parts with a thickness of 5~10cm: keep warm at 40~50℃ for 6~10h, and then heat up to 70~80℃ at a uniform rate and keep warm for 10~15h. C. Natural cooling: After drying, the oven is sealed and allowed to cool naturally to room temperature before removing the finished product.